THE HARMONIC CURRENTS GENERATED BY 6-PULSE , AC|DC CONVERTER WITH THE USE OF AC VOLTAGE REGULATOR (Journal of Engineering, 2008)
In this paper , a theoretical and experimental analysis of harmonic currents generated by 6-pulse, ac|dc converter with the use of ac voltage regulator is presented. The theoretical analysis is simulated using Fourier series analysis and Fast Fourier Transform ( FFT ) algorithm . The simulated analysis is validated with experimental results from 3-phase , 6-pulse , bridge converter rated at 4.2 Kw and connected to the 400 V , 50 Hz , ac power supply through a 3-phase , ac voltage regulator . The influence of dc load inductance on the ac harmonic current amplitudes is also evaluated.